The Relationship between Supply Chain Digitalization and Organizational Performance among the Electronics and Electrical Multinational Coporation Manufacturing Industries in Penang. - Cher Hao Xuan; Nor Kamariah Kamaruddin (Research in Management of Technology and Business, 2024)
In the new global economy, organizational performance in Electronics and Electrical (E&E) manufacturing industries has come to the forefront of business concerns, the awareness of Supply Chain Digitalization remains low among E&E manufacturing companies in Malaysia, posing a challenge to their organizational performance. Therefore, the purpose of the study is to identify the relationship between supply chain digitalization and organizational performance among the E&E multinational corporation (MNC) manufacturing industries in Penang. The quantitative method is used in this study which the questionnaire survey was distribited among the E&E MNC manufacturing industries. The target population consisted executive level such as professional, top-level managers, middle-level managers, lower-level managers, and professional in the E&E MNC manufacturing industries. The study comprises a sample size of 80 respondents, and the data collected through the questionnaire was analyzed utilizing SPSS for comprehensive insights and findings. The result showed a strong correlation relationship (r= 0.741) between supply chain digitalization and organizational performance among E&E MNC manufacturing industries in Penang. This research will be crucial to the E&E MNC manufacturing industries in order to improve organizational performance through the use of supply chain digitalization.